Strategi Penguatan Ekonomi Masyarakat Lokal Melalui Pembinaan Dan Pendampingan Bisnis Pada UKM Komunitas Himpunan Pengusaha Santri Indonesia - Nizar, Muhammad; Sukamto (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2022)
The purpose of service expected is based on the current explanation of the condition of the subject of service, among others, strengthening the SME financial structuring system that aims at efficiency and avoiding losses. All members have a good SME business concept and are in accordance with the scale of business based on SMEs becoming Benchmarks. The Indonesian Santri Entrepreneurs Association with the potential to export has increased in number. It has an effective marketing strategy concept so that products are known, favored and used by national and international parties. Expanding the HIPSI Silaturrahmi network by providing entrepreneurship education to students in general so that the pesantren involved are increasingly widespread throughout Indonesia. This service is carried out on the basis of a participatory model, in which the basic elements of the community empowerment / service process are: social participation and mobilization. The result of this dedication is a strategy undertaken to strengthen the economy of local communities by fostering SMEs in the Indonesian Santri Entrepreneurs Association, where the coaching includes managing the financial system, managing production time and efficiency in increasing productivity and increasing the profitability of SMEs, choosing profitable business concepts in determine supply chain members for start-up businesses, Seminar on small medium enterprized business practices according to Islamic sharia, build e-Commerce in SMEs using a variety of online-based media.